Evaluation of varieties and standardization of planting time in onion (Allium cepa L.) - Aruna S (Department of Vegetable Science, College of Horticulture, 2018)
Onion (Allium cepa L.) belonging to the family Alliaceae is one of the oldest vegetables in world and has been cultivated for more than 5000 years. It is an important and indispensable item in every kitchen as vegetable, spice and condiment. It is used as salad and cooked in various ways. Besides fresh consumption, onion provides a good raw material for processing industry as it can be processed in the form of dehydrated powder, rings, shreds, onion vinegar etc. The present experiment entitled “Evaluation of varieties and standardization of planting time in onion (Allium cepa L.)” was conducted at the Department of Vegetable Science, College of Horticulture, Vellanikkara during November-March, 2017-18. The major objectives of the study were to identify the best variety and planting time in onion for the plains of Kerala, and to study the effect of varieties, planting time and their interaction on the qualitative and quantitative traits of onion. Five onion varieties were evaluated in four different dates of planting with an interval of fifteen days which was commenced from 10 th November to 25th December 2017 in a split plot design with four replications. There were no variations among different dates of planting for qualitative traits such as bulb shape, bulb skin colour, bulb flesh color, etc. Vegetative characters such as plant height and leaf length were maximum in Arka Kalyan (50.47 cm and 46.47 cm respectively), whereas number of leaves was highest in Agrifound Dark Red (8.31). Leaf girth was maximum in Agrifound Light Red (3.35 cm). Among different dates of planting, plant height (51.05 cm) and number of leaves (8.50) were maximum in 10th December planting. Leaf length was highest in 25th November planting (46.60 cm) while leaf girth was maximum in 10th November planting (3.49 cm). Agrifound Dark Red recorded a minimum number of days (64.25) to reach 75% maturity. Among different planting dates, the plants in 10th December planting took minimum days (63.4) to reach 75% maturity. In the interactions between planting dates and varieties, Agrifound Dark Red planted on 10th December took minimum number of days (60) to reach maturity. Plant stand (39.63), neck thickness (4.16 cm) and bulbing percentage (70.76%) were highest in the variety Arka Kalyan. Average bulb weight varied significantly among different dates of planting. Highest average bulb weight was obtained when the planting was done on 25th November (66.2g). Average bulb weight ranged from 18g to 73.5g. There was no significant difference in number of scales among varieties, planting time and their interactions. Total Soluble Solids was highest in the variety, Agrifound Light Red (16.37°B). Among different planting dates, bulbs from 10th December planting recorded the highest TSS (16.92°B). Among the interactions, highest TSS was noted for Agrifound Light Red planted on 10th December (18.32°B). All the varieties were having medium to high pungency except Agrifound White in all the dates of planting. Total yield and marketable yield per plot varied significantly among different dates of planting. Among different dates of planting, marketable yield was highest in 25th November planting (0.96kg/plot). Among the interactions between varieties and planting dates, all the dates of planting except 25th Dec. were found to be statistically on par with respect to marketable yield for the varieties such as Arka Kalyan, Arka Pragati, Agrifound Dark Red and Agrifound Light Red. Planting on 25th Nov. and 10th Dec. were found to be superior and on par with respect to marketable yield in Agrifound White. All the five varieties can be recommended for commercial cultivation as they do not differ with each other with respect to marketable yield. Considering the consumer preferences, we can recommend Arka Kalyan and Agrifound Dark Red as they are having attractive dark red colour. The best time for transplantation was found to be 25th November, which was statistically on par with 10th November and 10th December. As a future line of work, more number of varieties are to be evaluated, nursery and crop management practices need to be standardised, and for conclusive results experiment has to be repeated.